Cumulative and Residual Effects of Paclobutrazol on Growth, Yield and Fruit Quality of ’Alphonso’ Mango - Reddy, Y T N; Kurian, Reju M (Journal of Horticultural Sciences, 2008)
A field experiment was conducted during 1996 to 2002 at Indian Institute of Horticultural Research, Bangalore, to study the cumulative and residual effects of paclobutrazol (PBZ) application on shoot vigour, flowering and fruit yield of seventeen years old ’Alphonso’ mango trees. Foliar sprays of the chemical at 500, 1000 or 2000 ppm or soil drench at 5 or 10 g a. i. per tree was given during September for three consecutive years and the residual effects were observed for three more subsequent years. Application of PBZ as soil drench was more effective than its foliar spray and doubled fruit yield during the six years. Chemical parameters of fruits such as TSS and acidity were not affected by the treatments but average weight of a fruit was less in the case of PBZ treatments. Residual influence of this chemical, when applied as soil drench, persisted in the three years following the discontinuation of application for three consecutive years, indicating the scope for skipping the application of PBZ or tapering down its dose after three years of its continuous application. From the results of this study, application of paclobutrazol at 5 g a.i. per tree as soil drench for three consecutive years and then its discontinuation for the subsequent three years appears to be most appropriate for ’Alphonso’ mango trees in the age group of about 15 to 25 years.